1985
DOI: 10.1073/pnas.82.1.236
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally restricted analogs of somatostatin with high mu-opiate receptor specificity.

Abstract: The cyclic tetradecapeptide somatostatin is known to interact with a variety of receptor systems over a wide concentration range (1). High-affinity (low dissociation constant) binding with a receptor system is generally thought to have physiological significance, but when the affinity is weak (micromolar), the physiological significance is not clear. The weak affinity that somatostatin displays for the opiate receptor is one such example. It We have prepared a number of conformationally restricted analogs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…Since peptide-induced scratching is mainly due to activation of opiate receptor systems (Van Wimersma Greidanus et al, 1985b;Spruijt et al, 1986a) this observation indicates that opiate receptors are involved in the behavioral response to SMS 201-995 and somatostatin. This is consistent with the suggestion by Terenius (1976) that somatostatin acts as partial agonistantagonist on opiate receptors in the CNS, and with other reports on opiate-like actions of somatostatin and some of its analogs (Rezek et al, 1978;Pelton et al, 1985). Interestingly, the contribution of the scratching element to SMS 201-995-induced grooming was most pronounced after doses ranging from 50 to 100 ng.…”
Section: Discussionsupporting
confidence: 92%
“…Since peptide-induced scratching is mainly due to activation of opiate receptor systems (Van Wimersma Greidanus et al, 1985b;Spruijt et al, 1986a) this observation indicates that opiate receptors are involved in the behavioral response to SMS 201-995 and somatostatin. This is consistent with the suggestion by Terenius (1976) that somatostatin acts as partial agonistantagonist on opiate receptors in the CNS, and with other reports on opiate-like actions of somatostatin and some of its analogs (Rezek et al, 1978;Pelton et al, 1985). Interestingly, the contribution of the scratching element to SMS 201-995-induced grooming was most pronounced after doses ranging from 50 to 100 ng.…”
Section: Discussionsupporting
confidence: 92%
“…One cysteine and one penicillamine (b,b-dimethylcysteine) residue were added to each end of the linear sequence to provide sulfhydryl groups for oxidative peptide cyclization. Penicillamine has been found to facilitate cyclization and provide greater conformational constraint relative to cysteine-cysteine cyclization (Pelton et al, 1985;Hruby et al, 1990). In the set of peptides listed in Figure 3, amino acid residues were added at either end in order to flank cysteine and penicillamine moieties in an effort to further restrain peptide conformation.…”
Section: Materials and Methods Peptide Synthesis Purification And Cmentioning
confidence: 99%
“…The observations that morphine increased the number of AM-IRpositive neurons by 22-36% but AM content by 208% in DRGs suggest that AM content in individual AM neuron was also increased. Similarly, an in vitro study showed that sustained exposure to morphine concentration-dependently increased AM level in cultured ganglion explants, an effect suppressed by the selective -opioid receptor antagonist CTAP (Pelton et al, 1985), whereas another selective -opioid receptor agonist, fentanyl, also upregulated AM synthesis. The finding that the morphineinduced increase in AM level is mediated through the activation of -opioid receptors is consistent with the purported role of this receptor subtype in the development of tolerance (Taylor and Fleming, 2001;Martini and Whistler, 2007).…”
Section: Discussionmentioning
confidence: 99%